Microbial Populations of Stony Meteorites: Substrate Controls on First Colonizers - Tait, Alastair W.; Gagen, Emma J.; Wilson, Sasha; Tomkins, Andrew G.; Southam, Gordon (Frontiers in Microbiology, 2017)
Finding fresh, sterilized rocks provides ecologists with a clean slate to test ideas about first colonization and the evolution of soils de novo. Lava has been used previously in first colonizer studies due to the sterilizing heat required for its formation. However, fresh lava typically falls upon older volcanic successions of similar chemistry and modal mineral abundance. Given enough time, this results in the development of similar microbial communities in the newly erupted lava due to a lack of contrast between the new and old substrates. Meteorites, which are sterile when they fall to Earth, provide such contrast because their reduced and mafic chemistry commonly differs to the surfaces on which they land; thus allowing investigation of how community membership and structure respond to this new substrate over time. We conducted 16S rRNA gene analysis on meteorites and soil from the Nullarbor Plain, Australia. We found that the meteorites have low species richness and evenness compared to soil sampled from directly beneath each meteorite. Despite the meteorites being found kilometers apart, the community structure of each meteorite bore more similarity to those of other meteorites (of similar composition) than to the community structure of the soil on which it resided. Meteorites were dominated by sequences that affiliated with the Actinobacteria with the major Operational Taxonomic Unit (OTU) classified as Rubrobacter radiotolerans. Proteobacteria and Bacteroidetes were the next most abundant phyla. The soils were also dominated by Actinobacteria but to a lesser extent than the meteorites. We also found OTUs affiliated with iron/sulfur cycling organisms Geobacter spp. and Desulfovibrio spp. This is an important finding as meteorites contain abundant metal and sulfur for use as energy sources. These ecological findings demonstrate that the structure of the microbial community in these meteorites is controlled by the substrate, and will not reach homeostasis with the Nullarbor community, even after ca. 35,000 years. Our findings show that meteorites provide a unique, sterile substrate with which to test ideas relating to first-colonizers. Although meteorites are colonized by microorganisms, the microbial population is unlikely to match the community of the surrounding soil on which they fall.